Drepanosticta emtrai sp. nov. from Vietnam with a discussion of Drepanosticta vietnamica Asahina, 1997 (Odonata: Zygoptera: Platystictidae) - Dow, Rory A.; Kompier, Tom; Phan, Quoc Toan (Zootaxa, 2018)
Drepanosticta emtrai sp. nov. is described from Vietnam (holotype male Ha Tinh Province, 9 vi 2015, to be deposited in RMNH). The new species is allied to D. carmichaeli (Laidlaw, 1915) and a number of other species of Drepanosticta including D. vietnamica Asahina, 1997. New illustrations of the paratype of D. vietnamica are provided and the species is discussed. The Drepanosticta carmichaeli-group, to which the above mentioned species belong, is defined and discussed.